Development of Digital Teaching Materials for Short Story Texts Based on Local Wisdom in Middle Schools (Phase D) - Yaqin, Ai Ainul; Gloriani, Yusida; Maschita, Dede Endang (International Journal of Educational Research Excellence (IJERE), 2024)
Education must integrate local wisdom to prevent cultural values ​​from fading in the era of globalization. The Merdeka Curriculum supports this with the flexibility to emphasize character education and independence. Digital teaching materials based on local wisdom, such as short story texts, can improve students' reading, writing and cultural understanding skills. The aim of this research is to develop and test digital teaching materials for short story texts based on local wisdom for junior high school students. This research used the ADDIE method with the help of 2 media and language validators as well as 6 students and 3 teachers in testing teaching materials. Data collection techniques were carried out using questionnaires, interviews and documentation. The teaching material design process begins with an analysis of student needs and the curriculum, followed by creating a storyboard and validation by two validators who state that the teaching material is very worthy of being tested. The implementation of local wisdom-based teaching materials shows high effectiveness, with student responses reaching 90% and teacher responses 87%, both in the very good category.